Economic adversity and entrepreneurship-led growth: Lessons from the Indian software sector - Suma Athreye (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
It is commonly believed that the business environment in developing countries does not allow productive technology-based entrepreneurship to flourish. In this paper, we draw on the experience of Indian software firms where entrepreneurial growth has belied these predictions. This paper argues that the business models chosen by Indian firms were those that best aligned the country's abundant labour resources and advantages to global demand. Many potentially higher value added opportunities struggled to attain success, but the qualitative value of experimental failures and the capability gaps they exposed was invaluable for collective managerial learning in the industry. Second, the paper also shows that the presence of growth opportunities and the success of firms stimulated institutional evolution to promote entrepreneurial growth. Last we show that the distinctive aggregate contribution of entrepreneurial firms was that they outperformed business houses and multinational subsidiaries in their more productive use of available capital resources whilst achieving similar levels of growth in output and employment. This paper draws upon an earlier shorter paper co-authored with Mike Hobday and titled Overcoming Development Adversity: How Entrepreneurs Led Software Development in India.
Keywords: L26; L86; O10; O32; O34; I28; 330; technology entrepreneurship; institutions and economic development; Indian software; intellectual property rights; Unternehmensgründung; Hochtechnologiesektor; Institutionelle Infrastruktur; Immaterialgüterrechte; Softwareindustrie; Indien